Development of Socio-Scientific Issue Learning Videos in Order to Support Education for Sustainable Development of Hydrocarbon and Petroleum Materials for High School Students Grade XI - Jayanti, A. A.; Dina, D.; Fillaeli, A. (Journal of Science Education Research, 2024)
This study aimed to develop learning videos based on socio-scientific issues in order to support education for sustainable development of hydrocarbons and petroleum materials for class XI Senior High School students. The method of the study was sequential exploratory mixed methods through the qualitative data collection stage, data analysis, and questionnaires. The developed videos contained three issues from the primary material in hydrocarbons and petroleum relevant to daily life. The created instructional videos are accessible online through the YouTube platform or via USB/Bluetooth file transfer. Usability and readability tests were performed to determine the feasibility of the generated learning videos; while the resulting percentages for usability and readability. Based on the result, videos were declared feasible by chemistry teachers and students at grade XI Senior High School so that videos can be used as the source of information based on the socio-scientific issue in order to support education for sustainable development of hydrocarbons and petroleum materials with usability and readability percentages respectively of 83.73% and 79.59%.